Tris (8-Hydroxyquinolinate) metals for solution-processed organic solar cells / Fahmi Fariq Muhammad - Muhammad, Fahmi Fariq (2012)
The simple fabrication process involving minimal material usage makes solutionprocessed organic solar cell (Courses) devices very attractive for harvesting solar energy. However, production of these devices on a commercial scale has been slow due to their relatively low power conversion efficiency and stability problems. It is expected that these obstacles will be surmounted in the future with rigorous studies actively being done in this field of research. Besides, a complete understanding of some basic electrical responses of these OSC devices has not been achieved yet. Consequently, seeking for interesting materials suitable for OSCs application and understanding the materials contribution are of great importance especially when strategies are targeted for the enhancement of OSCs. Tris (8-hydroxyquinolinate) metals (Mq3) are well known in the fabrication of stable organic light emitting diodes (OLEDs) and also for their unique optoelectronic properties. Very recently, tris (8-hydroxyquinolinate) aluminium (Alq3) prepared by thermal evaporation has been used as a buffer layer and dopant material to improve the performance of OSCs. However, its employment in solution-processed organic solar cells is still rare. Little attention has been paid on the behaviour of this material when applied in organic solar cells. Therefore, benefiting from the properties of Mq3 and easy fabrication process of solution-processed organic solar cell, the current thesis is focused on characterizing the OSCs related physical properties of tris (8- hydroxyquinolinate) gallium (Gaq3) and aluminium (Alq3) (as representatives of the Mq3 materials) and then applying them in solution-processed organic solar cells. The solution-processed OSC devices are based on ternary bulk heterojunction structure (three components blended all together) of dihexylisexithiophen/Mq3/methanofullerene (DH6T/Mq3/PCBM). The optoelectronics, spectroscopic, electrochemical, structural, morphological, and thermal properties of Mq3 materials are first investigated before incorporating them into the photovoltaic active layers of the devices. From the analysis of physical properties of Mq3 materials as well as the assessment on the electrical characteristics of the devices, this work suggests that Mq3 can be a good candidate to be applied in solution-processed OSCs. The photovoltaic and electrical characteristics of the devices demonstrated that the photocurrent, open circuit voltage, and the performance of the devices have improved by approximately six times compared to the devices without Mq3 incorporation. The basic contribution of Mq3 materials for this improvement is believed to originate from the increase in the number of exciton generation and their dissociation into free charge carriers. This can be due to the enlarged area of the donor-acceptors boundaries between each of the DH6T/Mq3 and DH6T/PCBM moieties, thereby broadening the absorption of photons. Next, Mq3 incorporation can result in the stabilization of the mobility of the charge carriers within the DH6T donor and Mq3/PCBM acceptors producing a balanced transportation for the holes and electrons. The results indicated promising approaches for Mq3 materials to be applied in solution-processed OSCs as incorporation of Mq3 into the devices active layers considerably enhanced the overall performance and reproducibility of these devices.